ESTIMASI NILAI HERITABILITAS BERAT LAHIR, SAPIH, DAN UMUR SATU TAHUN PADA SAPI BALI DI BALAI PEMBIBITAN TERNAK UNGGUL SAPI BALI - Kaswati (Kaswati); Sumadi (Sumadi); Nono Ngadiyono (Buletin Peternakan, 2013)
The study was conducted to estimate heritability (h2) of birth eight, weaning weight and yearling weight of Bali Cattle at Balai Pembibitan Ternak Unggul (BPTU) Sapi Bali. This study used pedegree record including birth weight, weaning weight and yearling weight (365 days) from 2006 to 2009 years. The recording of pedigree were collected from 150 Bali calves which inherited from the crossing between 9 bulls and 150 dams. The estimation of heritability were analysed by Paternal Halfsib Correlation method. The results indicated the heritability of birth weight, weaning weight and yearling weight were 0.85±0.44; 0.51±0.32 and 0.54±0.32 respectively. Inconclusion, heritability of birth weight, weaning weight and yearling weight of Bali Cattle at BPTU Sapi Bali remain in high level.(Key words: Bali cattle, Birth weight, Heritability, Weaning weight, Yearling weight)